PENGARUH PRODUK, HARGA, PROMOSI DAN TEMPAT TERHADAP KEPUTUSAN PEMBELIAN PRODUK SALON KECANTIKAN (Studi Pada Rumah Cantik Arlova Di Kec. Blega Kab. Bangkalan) - Mukarromah Mukarromah; Suyono Suyono (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This research aims to know and analyze: 1. Product influence on decision of purchase of product product rca 2. The price of product purchase decision on the rca 3 beauty salon decision. The influence of the promotion on the decision to buy products from the rca 4 beauty parlor. Impact on the decision of purchasing products from the rca beauty parlor. Retrieval. The study was conducted with a kind of quantitative research using primary and secondary data. The technique for taking a sample sample is random sampling. Data from the rca customers as many as 84 of those who bought rca products during July through September 2020. This research data analysis technique USES the t test and test f using SPSS version 23. The results of the t-test known products, promotions and places are inherently positive and significant to the decision of the purchase while the price is substantially positive and insignificant to the decision of the purchase. While the results of the known f test results, prices, promotions and places together (simultaneous) affect the decision of the purchase.